The Influence of Reading Ability on the Results of the Students' Presentation in German - Diah Ayu Sukma Wahyuning Putri; Deddy Kurniawan (Universitas Negeri Malang, 2020)
The aim of this study is to describe the reading ability of the students in Freier Vortrag course at German Department State University of Malang and the influence of reading ability on the students' presentation results. Based on the data collection, the average reading ability is 58 and the presentation result is 75. The independent sample test gives a sig. rating 0.000 less than 0.05. It means that Ha is accepted,